2006
DOI: 10.1108/10569210680000215
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of customer loyalty: An analysis of intangible factors in three service industries

Abstract: The purpose of this study is to investigate how customers' perceptions of service quality, product quality, and price fairness influence their loyalty to a particular service provider. Based on the results of a pilot study, we have elected to study banks, auto repair and maintenance shops, and (gasoline) filling stations, each of which are characterized by differing degrees of intangible service provision. Our results show that customer satisfaction either fully or partially mediates the relationship between c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
60
1
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 47 publications
8
60
1
8
Order By: Relevance
“…The results of several studies indicate that service quality has a positive effect on satisfaction [5], [6], [7], [8]. One of these studies found that service quality has a positive significant impact on customer satisfaction.…”
Section: Service Qualitymentioning
confidence: 99%
“…The results of several studies indicate that service quality has a positive effect on satisfaction [5], [6], [7], [8]. One of these studies found that service quality has a positive significant impact on customer satisfaction.…”
Section: Service Qualitymentioning
confidence: 99%
“…(Bei & Chiao, 2006;Choi & Chu, 2001;Riadh, 2012;Xiaoyun Han, Kwortnik, & Chunxiao Wang, 2008). Satisfaction with a service experience is both cognitive (evaluative) and an affectivebased response.…”
Section: The Lodging Quality Index and Its Relation To Customer Satismentioning
confidence: 99%
“…A library query presents that in literature, we may encounter numerous papers on the factors that are shaping the loyalty of customers taking advantage of automobile services [25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…The next researchers analyzed determinants forming customer loyalty on the basis of three services industries, including automobile repairs [27]. The influence of the quality of the product, quality of services, and fair prices exerted on the loyalty has been examined.…”
Section: Introductionmentioning
confidence: 99%